Shari'a in Europe - Rohe, Mathias; Caeiro, Alexandre; Tsitselikis, Konstantinos (Die Welt des Islams, 2004)
Rohe, Mathias: Application of shari'a rules in Europe: scope and limits. - S. 323-350 Caeiro, Alexandre: The social construction of shari'a: bank interest, home purchase, and Islamic norms in the West. - S. 351-375 Hussain, Dilwar: Muslim political participation in Britain and the "Europeanisation" of fiqh. - S. 376-401 Tsitselikis, Konstantinos: The legal status of Islam in Greece. - S. 402-431